Perfectionism: Theory, Research, and Treatment. 2002
DOI: 10.1037/10458-010
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional attitudes, perfectionism, and models of vulnerability to depression.

Abstract: The past 30 years have seen a fundamental shift in how psychopathology is understood, from a reliance on symptom-based psychiatric definitions to a greater emphasis on the phenomenology and basic mental operations underlying various forms of emotional disturbance. Much of the change in theory and therapy was set in motion by the original cognitive formulation of depression (Beck, 1967), an approach that over time has been extended to virtually the entire range of clinical problems. Specific domains within this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 81 publications
1
46
0
2
Order By: Relevance
“…Table 1 Zero-order and semipartial correlations of perfectionism, need for approval, pure perfectionism, and pure need for approval with the NEO-PI-R five-factor summary scores DAS Perfectionism in Relation to the NEO-PI-R. Contrary to the prevailing assumption that DAS perfectionism primarily refers to high personal standards and motivation to attain Table 2 Zero-order and semipartial correlations of perfectionism, need for approval, pure perfectionism, and pure need for approval with the neuroticism, extraversion, openness, agreeableness, and conscientiousness facets perfection (e.g., Brown & Beck, 2002), the present study adds to recent studies indicating that DAS perfectionism actually more closely resembles the primarily maladaptive, self-critical aspects of the perfectionism construct (Shahar & Priel, 2003;Sherry et al, 2003). DAS perfectionism was not significantly positively related to the conscientiousness domain and facets in contrast to selforiented perfectionism, which has been primarily positively related to the conscientiousness domain and facets, especially achievement striving (Hill et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 Zero-order and semipartial correlations of perfectionism, need for approval, pure perfectionism, and pure need for approval with the NEO-PI-R five-factor summary scores DAS Perfectionism in Relation to the NEO-PI-R. Contrary to the prevailing assumption that DAS perfectionism primarily refers to high personal standards and motivation to attain Table 2 Zero-order and semipartial correlations of perfectionism, need for approval, pure perfectionism, and pure need for approval with the neuroticism, extraversion, openness, agreeableness, and conscientiousness facets perfection (e.g., Brown & Beck, 2002), the present study adds to recent studies indicating that DAS perfectionism actually more closely resembles the primarily maladaptive, self-critical aspects of the perfectionism construct (Shahar & Priel, 2003;Sherry et al, 2003). DAS perfectionism was not significantly positively related to the conscientiousness domain and facets in contrast to selforiented perfectionism, which has been primarily positively related to the conscientiousness domain and facets, especially achievement striving (Hill et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the NEO-PI-R, sociotropy has been strongly related to neuroticism, especially the self-consciousness facet, along with the agreeableness facets of compliance, modesty, and tender-mindedness, and negatively related to the assertiveness facet of extraversion (Bagby et al, 2001;Dunkley et al, 1997). However, it is noteworthy that the DAS perfectionism and need for approval scales are substantially correlated which indicates to some degree a lack of specificity between them (e.g., Blaney & Kutcher, 1991;Blatt et al, 1995) that might limit the degree of correspondence between DAS need for approval and sociotropy/ dependency in relation to the NEO-PI-R. Brown and Beck (2002) suggested that DAS need for approval reflects an interpersonal sort of perfectionism because the need for approval items (e.g., ''If others dislike you, you cannot be happy'') reflect a rigid, inflexible, and absolute thinking style similar to the perfectionism factor items (e.g., ''If I fail at my work, then I am a failure as a person'').…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to the prevailing assumption that DAS perfectionism primarily refers to high PS and motivation to attain perfection [9], DAS perfectionism recently has b een demonstrated to more closely reflect SC perfectionism than PS perfect ionism [10,11]. In relation to the 5-factor model of person ality [12], DAS perfect ionism and other SC perfectionism measures have been related to neuroticism, introversion, and antagonism, whereas PS perfectionism measures are most closely associated with conscientiousness [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Do sada su u istraživanjima kao medijatori odnosa perfekcionizma i subjektivnog blagostanja (u celini, kao i u odnosu na njegove pojedinačne komponente) sagledavane varijable poput načina na koji osoba opaža i doživljava stres (Chang, 2000;Chang, 2006;Rice, Vergara, & Aldea, 2006), kao i načina na koji pokušava da ga prevlada (Wei, Heppner, Russel, & Young, 2006), dok je uloga kognitivnih činioca kao potencijalnih medijatora ovog odnosa slabije razmatrana (Chang, 2000). U studijama koje su se bavile ispitivanjem veza kognitivnih karakteristika sa pozitivnim i negativnim formama perfekcionizma, te sa pozitivnim i negativnim psihološkim ishodima, kognitivne karakteristike su uglavnom sagledavane specifično i usko, najčešće u vidu kognitivnih distorzija i stereotipnog načina razmišljanja (Bergman et al, 2007;Brown & Beck, 2002;Burns & Fedewa, 2005). Malo je istraživanja u kojima je ispitivan odnos pozitivnog i negativnog perfekcionizma sa subjektivnim blagostanjem pri čemu su kao potencijalni medijatori razmatrani optimizam i pesimizam, a shodno pomenutom teorijskom modelu i dosadašnjim empirijskim nalazima, čini se opravdanim pretpostavka da upravo oni mogu imati medijacionu ulogu u relaciji ovih varijabli.…”
Section: Optimizam I Pesimizam Kao Medijatori Odnosa Perfekcionizma Iunclassified